Current status and reflections on the diagnosis and treatment of respiratory tract infections in children in the COVID‐19 pandemic and post‐COVID‐19 era - Yuyi Tang; Luo Ren; Enmei Liu (Wiley, 2023)
Abstract Respiratory tract infections (RTIs) are common and frequently occurring diseases in children, posing a significant health threat to children worldwide. Viruses are the most important pathogens of childhood RTIs. Since the outbreak of Coronavirus Disease 2019 (COVID‐19), a series of nonpharmaceutical interventions (NPIs) have been widely implemented around the globe, and important changes have taken place in the spectrum of respiratory diseases and viruses in children. However, with relaxation of NPIs, there has been a "virus resurgence" in some areas, with multiple viral infectious diseases appearing simultaneously. This review comprehensively summarizes the changes observed in the spectrum of respiratory diseases and viruses in children in the context of the COVID‐19 pandemic, explores possible mechanisms, and presents reflections on the key points of diagnosis and treatment of RTIs in children in the post‐COVID‐19 era in light of recent advances in COVID‐19 in children.